2020
DOI: 10.1002/chem.202000016
|View full text |Cite
|
Sign up to set email alerts
|

Hydride Transfer to Gold: Yes or No? Exploring the Unexpected Versatility of Au⋅⋅⋅H−M Bonding in Heterobimetallic Dihydrides

Abstract: The potential for coordination and H-transfer from Cp2MH2 (M = Zr, W) to gold(I) and gold(III) complexes was explored in a combined experimental and computational study. [(L)Au] + cations react with Cp2WH2 giving [(L)Au(κ 2 -H2WCp2)] + (L = IPr (1), cyclic (alkyl)(amino)carbene (2), or phosphines PPh3 (3) and Dalphos-Me (4) [IPr = 1,3-bis(diisopropylphenyl)imidazolylidene; Dalphos-Me = di(1-adamantyl)-2-(dimethylamino)phenyl-phosphine], while [Au(DMAP)2] + (DMAP = p-dimethylaminopyridine) affords the C2-symmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 115 publications
6
36
0
Order By: Relevance
“…Rocchigian, Bochmann and Hrobárik et al reported recently on the different coordination modes of Cp2WH2 at Au(I)/Au(III) cations. 61 In the case of asymmetric hydride coordination a comparable 1 H NMR spectrum was observed: -11.4 ppm, JW-H 48 Hz, -9.6 ppm, JW-H 61 Hz. 61 Furthermore, chemical exchange of all hydrides in cations 3 was proven by 1 H-1 H EXSY NMR studies.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Rocchigian, Bochmann and Hrobárik et al reported recently on the different coordination modes of Cp2WH2 at Au(I)/Au(III) cations. 61 In the case of asymmetric hydride coordination a comparable 1 H NMR spectrum was observed: -11.4 ppm, JW-H 48 Hz, -9.6 ppm, JW-H 61 Hz. 61 Furthermore, chemical exchange of all hydrides in cations 3 was proven by 1 H-1 H EXSY NMR studies.…”
Section: Resultsmentioning
confidence: 79%
“…61 In the case of asymmetric hydride coordination a comparable 1 H NMR spectrum was observed: -11.4 ppm, JW-H 48 Hz, -9.6 ppm, JW-H 61 Hz. 61 Furthermore, chemical exchange of all hydrides in cations 3 was proven by 1 H-1 H EXSY NMR studies. For the characterization of the isomers by 119 Sn, 207 Pb and 183 W NMR spectroscopy see Table 1 and the SI.…”
Section: Resultsmentioning
confidence: 79%
“…In agreement with this, no reaction occurred between H 2 (1 bar, −10 °C) and ether-free 30. However, with the ether adduct 28 H−H cleavage takes place within a few hours at −20 °C, via an [LAu + 216 In addition to these σ-bonded species formed en-route to H−E bond activation, the question whether gold compounds are able to form hydrogen bonds of the type D−H (+) •••M has attracted significant attention recently. 217−222 In such arrangements D is an electron-rich donor atom covalently bonded to H, and M possesses an electron pair capable of acting as proton acceptor, to give a 4-electron-3-center interaction.…”
Section: Trans-effect/trans-influencementioning
confidence: 99%
“…Relativistic DFT calculations showed the presence of electron density along the Au–W vector of 64 and its absence in the case of 65 . The calculations also showed that in all of these gold hydride complexes the W–H bond is polarized but remains present and strong, while true covalent Au–H bonds are not yet formed …”
Section: General Aspects Of Gold(iii) Coordination Chemistrymentioning
confidence: 99%
“… The Lewis basic behavior that gold displays in such complexes is further illustrated by the recent demonstration that adequately substituted gold­(I) centers are prone to protonation or amenable to the formation of Au···H-X HBs (HB = hydrogen bond, X = electronegative element) . The formation of Au···H–X interactions was originally supported by calculations as in the case of C , and later experimentally verified for cationic derivatives such as D and E . The stability of such HBs benefits from the metallobasic character of gold as well as its electronegativity, which strengthens the charge transfer and Coulombic term of the Au···H–X interaction, respectively. Dispersion forces, enhanced by relativistic effects at gold, are also invoked as substantial contributors…”
mentioning
confidence: 86%